If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 7sin(3(x + 4)) + 2 Reorder the terms: y = 7ins(3(4 + x)) + 2 y = 7ins((4 * 3 + x * 3)) + 2 y = 7ins((12 + 3x)) + 2 y = (12 * 7ins + 3x * 7ins) + 2 y = (84ins + 21insx) + 2 Reorder the terms: y = 2 + 84ins + 21insx Solving y = 2 + 84ins + 21insx Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 2 + 84ins + 21insx
| -17=-2n-13-8n | | -4x-33=42-9x | | (14x-1)+(8x-7)=78 | | 20t+.15=30t+.10 | | 6y+12+2y=5y-2 | | 61=2x+17+x+17 | | 2n=10.06 | | 70=7x | | (2x-5)=-6 | | 9.5=v+2.8 | | 8x-6=3x+24 | | (2x-5)=6 | | 15x-8x=49 | | 12*c=108 | | 7y+8=-2y | | 2v+28=16+-4(v+7) | | -2(g+8)=64 | | -2-m=7 | | 4x^2=3x^2+9 | | 5(f-4)=-10 | | -5+5x=35 | | (x-2)=-2x-1 | | 8g-32=4g+16 | | X+17+4x=-29-4x-35 | | 1halfr+6=3-2r | | -10(s+3)=-71 | | (5x^3-6x^2+2x)+(-4x^2+3x)=42 | | 35x^2+76x+32= | | -10(s+3)=71 | | (x-5)=-6x-10 | | 3-2x^2=21 | | 10=-0.15x^2+3x |